PENGEMBANGAN PERANGKAT PEMBELAJARAN MATEMATIKA BERBASIS PENDEKATAN KONTEKSTUAL PADA MATERI SISTEM PERSAMAAN LINEAR DUA VARIABEL UNTUK PESERTA DIDIK KELAS VIII SMP/MTs - Rizka Rizka (Departemen Matematika, 2021)
The purpose of this study was to develop a mathematics learning tool in the form of lesson plans and handouts based on a contextual approach to the valid and practical material on a two-variable system of linear equations for class VIII SMP/MTs students. This research used the plomp model. The plomp model consists of a preliminary research and development of prototype or prototyping phase. Needs analysis, curriculum analysis, concept analysis, and student analysis were carried out at the preliminary research stage to obtain information about the characteristics needed in developing learning tools. The development or prototyping stage is carried out by making prototypes of learning tools in the form of lesson plans and handouts based on a contextual approach through formative evaluation stages. The steps in the formative evaluation carried out were self evaluation, expert review, one to one evaluation, and small group evaluation. The results of this study indicate that learning tools in the form of lesson plans and handouts based on a contextual approach are included in the very valid category with a validity level of 88.25% for lesson plans and 88.43% for handouts. Then, the results of the Handout research are based on a very practical category of contextual approach with a practicality level of 91.25% by students and 93.83% by teachers. Keywords– Development of learning tools, Contextual approach, System of Linear Equations of Two Variables